Microsoft SQL Server 2005 performance optimization and tuning handbook - England, Ken, 1955-; Powell, Gavin (Boston, Mass. ; Oxford : Digital, 2007)
Database professionals will find that this new edition aids in mastering the latest version of Microsofts SQL Server. Developers and database administrators (DBAs) use SQL on a daily basis in application development and the subsequent problem solving and fine tuning. Answers to SQL issues can be quickly located helping the DBA or developer optimize and tune a database to maximum efficiency. Basic questions are easily located on the topics of filtering, sorting, operators, conditionals, pseudo columns, single row functions, joins, grouping functions, sub queries, composite queries, hierarchies, flashback queries, parallel queries, expressions and regular expressions. Assistance on DML, data types (including collections), XML, DDL for basic database objects such as tales, views and indexes, partitioning, and security is also considered. * Identifies the most common issues DBAs face day to day for easy reference *Provides DBAs with solutions actually used by the authors in enterprise environments to resolve common and specialized problems to optimization issues. * Addresses issues that have been introduced by new features which can add more control but reduce performance.
Keywords: SQL server; Client/server computing; Relational databases; Electronic books